The Description Ability of Auditory Hallucinations Patients in Self Care Fulfillment - Sulistyorini, Ariani; Putri, Betika Yulia (Journal Of Nursing Practice, 2019)
Background: Auditory hallucinations are the inability of humans to distinguish internal stimuli (thoughts) and external stimuli (outside world). Hallucination clients give perceptions or opinions about the environment without any real objects or stimuli. And it affects the patient's ability to meet their needs, including the ability to fulfill self-care. Ability is the ability, skill, strength of a person to work on their own. Purpose: The purpose of the study was to describe the ability of auditory hallucinatory patients in self-care fulfillment.Method: The design research is descriptive, population and research sample of 20 respondents, with total sampling technique, research instruments in the form of cheklish, this study was conducted on 13 May-13 June 2019 using a single variable is the describe ability of auditory hallucinatory patients in self-care fulfillment. Data is analyzed by percentage and interpreted quantitatively.Result: The results of the study were obtained from 20 respondents, most of the respondents 13 respondents (65%) were able to perform self-care well, a small portion of respondents 3 respondents (15%) had sufficient self-care ability, half of respondents 4 respondents (20%) had the ability lack of self care.Conclution: Self-care ability in patients Hearing hallucinations are influenced by age, sex, education, occupation, marital status, living with family, duration of suffering, history of hospitalization, taking medication and medication history. It is expected that auditory hallucinosis patients are willing and able to perform self-care properly and optimally to maintain personal hygiene and the environment